GREEN CHEMISTRY DALAM DESAIN PEMBELAJARAN PROJECT-BASED LEARNING BERBASIS KARAKTER DI MADRASAH ALIYAH SE-KABUPATEN DEMAK - Saptorini, Saptorini; Widodo, A.T.; Susatyo, E.B. (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2014)
Difficulties experienced by chemistry teachers in Islamic Senior High Schools due to limited laboratory facilities and learning supports encourage the implementation of this activity. A character-based PBL-Green Chemistry learning model is expected to increase students’ creativity and characteristics. The method used in this activity was seminar and workshop, followed by participant feedback. Participants were then divided into groups to develop a PBL-green chemistry lesson plan together with the project products in accordance with the selected topic. These were given feedback and assessment from the team. Opinions and responses of participants to the enforceability of this activity has been done by distributing questionnaires filled out by the participants. This activity was able to increase the ability of 66.7% of chemistry teachers in Demak designing a character-based PBL-green chemistry learning design in chemistry topics at good category. This activity was able to grow the participants’ commitment to continue to create and innovate for the national education in Indonesia. However, the seriousness of teachers in trying to be creative with the project products still needs to be improved.